2016
DOI: 10.1111/soru.12130
|View full text |Cite
|
Sign up to set email alerts
|

Rural Second Homes: A Narrative of De‐Centralisation

Abstract: The dominant political narrative in Norway over the past half century maintains that the country is facing major challenges due to centralisation and urbanisation of the population. Responding to this assumption, this article argues that a significant segment of the population is in fact spending more time in rural areas when we consider the impact of second home mobility. This argument is based on a theoretical review of the ontological trajectories of settlement and mobility. Set in a rural-urban perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
1
21
0
2
Order By: Relevance
“…Hence, it has been argued and shown that clear distinctions between primary and second homes as well as permanent and temporary inhabitants are increasingly problematic, not least because of a growing mobility blurring borders between categories (Barnett, 2014;Farstad & Rye, 2013;Gallent, 2007;Jennings & Krannich, 2013;Persson, 2015). Ellingsen (2017) even argues that the study of rural development should always include second home mobility, since it is an integrated part of rural demography and economy. There is also evidence that rural populations perceive second home tourism far more positively than previously anticipated (Rye, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it has been argued and shown that clear distinctions between primary and second homes as well as permanent and temporary inhabitants are increasingly problematic, not least because of a growing mobility blurring borders between categories (Barnett, 2014;Farstad & Rye, 2013;Gallent, 2007;Jennings & Krannich, 2013;Persson, 2015). Ellingsen (2017) even argues that the study of rural development should always include second home mobility, since it is an integrated part of rural demography and economy. There is also evidence that rural populations perceive second home tourism far more positively than previously anticipated (Rye, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Often, in these cases, the lines are drawn based on residence frequency (permanent or summer resident) or residence history (in-migrant or in-born). In several studies, in-migrants (or incomers), second home-owners and 'native' inhabitants are separated as different groups within a community (Ellingsen, 2017;Gieling et al, 2019). Our data show that these distinctions were really ambiguous, and the notion of a 'native' resident and incomer was fluid.…”
Section: Paradoxes Of Representations Of the 'Rural' And 'Community'mentioning
confidence: 64%
“…Moreover, mobility is just as much about moving as it is about decisions to stay put; mobility is also about islands of waiting during the movements (Cresswell, 2010, p. Maclaren, 2018). In a similar vein, changes on the administrative level mould norms and representations, affecting thus also sociomaterialities of locations (Ellingsen, 2017).…”
Section: Theorizing (Im)mobile Communitiesmentioning
confidence: 95%
“…Lokaliseringsmessig ligger feltene typisk fra to til fire kjøretimer fra sentrale byregioner: Oslo, Stavanger, Bergen og Trondheim (Ellingsen, 2016;Overvåg, 2011;Overvåg & Arnesen, 2007) -det vi kan kalle for hinter landseffekten. Dette er et mønster som er lett synlig i kartet i figur 4 -og i figur 2 som viser hvor de bor, husholdningene som eier fritidsboliger i fjellområdet.…”
Section: Overalt?unclassified